The Use of Webbing Technique to Improve Recount Text Writing Achievement of Tenth Graders of SMAN 1 Curup Selatan - Utari, Astin (Linguists : Journal of Linguistics and Language Teaching, 2019)
This study was aimed at examining the efficacy of webbing technique to help students improving their writing achievement in recount text. This research was used experimental method. The population was the tenth graders of SMAN 1 Curup Selatan in academic years 2016/2017 and 30 students were taken as the sample by using convenience sampling. The result showed that there was any significant improvement with a significant mean difference of 11.72 (t=.000) and its aspects. It was also supported the results of questionnaire which indicated webbing was useful technique to solve students’ problems in writing recount texts.These results indicated that webbing technique is effective in improving the students’ writing achievement.  Keywords:, webbing technique, writing  achievement, recount text